1987
DOI: 10.1111/j.1600-0447.1987.tb02940.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal activity in antidepressant medicated and unmedicated depressive patients and in matched healthy subjects

Abstract: A group of 59 depressive in- and outpatients displayed statistically significantly subnormal electrodermal activity (EDA) according to the skin conductance level, the skin conductance response magnitude, the skin conductance response rate, and the index of nonresponding during neutral tone stimulation, compared to 59 mentally and somatically healthy subjects, individually matched for age and sex. Comparisons between 20 antidepressant medicated and 20 unmedicated patients, matched for age, and comparisons betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…Thus, the lower SCL, OR and SCOR conductance amplitudes are, the larger the scores in BDI, STAI-E and STAI-R. Some authors have observed similar results [34,42], but other studies have not detected any correlation [26,38,43,44]. In the present research, the depressive sample displayed high scores in STAI which would be able to reflect elevated anxiety.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, the lower SCL, OR and SCOR conductance amplitudes are, the larger the scores in BDI, STAI-E and STAI-R. Some authors have observed similar results [34,42], but other studies have not detected any correlation [26,38,43,44]. In the present research, the depressive sample displayed high scores in STAI which would be able to reflect elevated anxiety.…”
Section: Discussionsupporting
confidence: 70%
“…Nonetheless, lower basal conductance levels and lower conductance amplitudes were detected in depressive patients, even after 1 month free of antidepressive drugs [19,33,34]. Moreover, Iacono et al [24] and William et al [35] compared depressive patients with antidepressive treatment to those without, finding no significant differences.…”
Section: Discussionmentioning
confidence: 96%
“…(Almost all patients were on antidepressants.) For example, there is evidence that antidepressants weaken SCRs (e.g., Thorell, Kjellman, & d'Elia, 1987). In addition, while the cognitive effects of antidepressants are still unclear, they might have had some effects on attentional processing or on other physiological responses.…”
Section: Discussionmentioning
confidence: 97%
“…Under these circumstances, the LTL reacts with depressive affect (Bear & Fedio, 1977) when the right hemisphere interprets the situation as presenting the possibility of failure. Just as in the case of depression, this reaction reduces the arousal response (Albus et al, 1987;Iacono et al, 1983;Thorell et al, 1987;Williams et al, 1985).…”
Section: Discussionmentioning
confidence: 94%
“…In fact, even temporary sodium amytal inactivation of the left hemisphere is associated with negative mood states (Christianson, Saisa, Garvill, & Silfvenius, 1993). Depressive affect is associated with reductions in electrodermal activity (Albus, Muller, Ackenheil, & Engel, 1987;Iacono, Lykken, Peloquin, Lumry, Valentine, & Tuason, 1983;Thorell, Kjellman, & D'Elia, 1987;Williams, Iacono, & Remick, 1985), heart rate (Albus et al, 1987;Pignatiello, Camp, Elder, & Rasar, 1989), and reaction time (Hill & Dutton, 1989;. As a result, we hypothesized that LTLs would exhibit hypoarousal, rather than hyperarousal, in a successlfailure performance paradigm, where the possibility of failure would be likely to activate their depressive tendency.…”
mentioning
confidence: 97%